Effectiveness of Sexuality education program in reducing the risk of teenage pregnancy - Anna Uswatun Qoyyimah; Yenni Kristiana; Tri Budi Rahayu; Novian Aldo (PT. Anagata Sembagi Education, 2024)
This study aims to assess the effectiveness of sexuality education programs in reducing the risk of teenage pregnancy. Using a quantitative survey method, data were collected from 220 adolescent respondents to evaluate their knowledge, attitudes, and behaviors related to sexual health before and after participating in the program. The survey focused on key aspects such as knowledge of reproductive health, sexual behavior, and contraceptive use. Statistical analysis was conducted to determine if there were significant changes in participants' attitudes and behaviors following the intervention. The findings of this research are expected to provide valuable insights into the impact of sexuality education on teenage pregnancy rates and offer recommendations for improving the design and implementation of such programs.